Is there a higher genetic load of susceptibility loci in familial ankylosing spondylitis? - Joshi, R; Reveille, J; Brown, M; Weisman, M; Ward, M; Gensler, L; Wordsworth, B; Evans, D; Assassi, S (2012)
Several genetic risk variants for ankylosing spondylitis (AS) have been identified in genome-wide association studies. Our objective was to examine whether familial AS cases have a higher genetic load of these susceptibility variants.Overall, 502 AS patients were examined, consisting of 312 patients who had first-degree relatives (FDRs) with AS (familial) and 190 patients who had no FDRs with AS or spondylarthritis (sporadic). All patients and affected FDRs fulfilled the modified New York criteria for AS. The patients were recruited from 2 US cohorts (the North American Spondylitis Consortium and the Prospective Study of Outcomes in Ankylosing Spondylitis) and from the UK-Oxford cohort. The frequencies of AS susceptibility loci in IL-23R, IL1R2, ANTXR2, ERAP-1, 2 intergenic regions on chromosomes 2p15 and 21q22, and HLA-B27 status as determined by the tag single-nucleotide polymorphism (SNP) rs4349859 were compared between familial and sporadic cases of AS. Association between SNPs and multiplex status was assessed by logistic regression controlling for sibship size.HLA-B27 was significantly more prevalent in familial than sporadic cases of AS (odds ratio 4.44 [95% confidence interval 2.06, 9.55], P = 0.0001). Furthermore, the AS risk allele at chromosome 21q22 intergenic region showed a trend toward higher frequency in the multiplex cases (P = 0.08). The frequency of the other AS risk variants did not differ significantly between familial and sporadic cases, either individually or combined.HLA-B27 is more prevalent in familial than sporadic cases of AS, demonstrating higher familial aggregation of AS in patients with HLA-B27 positivity. The frequency of the recently described non-major histocompatibility complex susceptibility loci is not markedly different between the sporadic and familial cases of AS.